An Analysis of Netizens’ Hate Comments Toward Joe Biden’s Speech “Biden Delivers Memorial Day Message” on Fox News’s YouTube Channel (PANOPTICON: Journal of English Studies, 2026)
This study aims to examine how social bias and toxicity are manifested in hate speech directed at Joe Biden’s speech on YouTube. The object of this study is the comments section of the video entitled “Biden Delivers Memorial Day Message” published in 2024 on Fox News’s YouTube channel. This study employs a qualitative descriptive method, with data collected through in-depth reading and analysis of words, phrases, and sentences found in the comments. The study applies Won’s theory (2001), which identifies two types of bias—gender bias and other biases—and three types of toxicity: hate, insult, and offensive expression. The findings reveal that 11 instances of bias were identified in the comments, with “other biases” being the most dominant type. Additionally, 69 instances of toxicity were found, with insults emerging as the most frequent category. The dominance of other biases and insults suggests that hate comments on social media tend to focus on personal attacks against the speaker as a way of expressing anger and hostility, rather than critically engaging with the content of the speech itself.